16=4p(3-p)

Simple and best practice solution for 16=4p(3-p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 16=4p(3-p) equation:


Simplifying
16 = 4p(3 + -1p)
16 = (3 * 4p + -1p * 4p)
16 = (12p + -4p2)

Solving
16 = 12p + -4p2

Solving for variable 'p'.

Reorder the terms:
16 + -12p + 4p2 = 12p + -12p + -4p2 + 4p2

Combine like terms: 12p + -12p = 0
16 + -12p + 4p2 = 0 + -4p2 + 4p2
16 + -12p + 4p2 = -4p2 + 4p2

Combine like terms: -4p2 + 4p2 = 0
16 + -12p + 4p2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(4 + -3p + p2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(4 + -3p + p2)' equal to zero and attempt to solve: Simplifying 4 + -3p + p2 = 0 Solving 4 + -3p + p2 = 0 Begin completing the square. Move the constant term to the right: Add '-4' to each side of the equation. 4 + -3p + -4 + p2 = 0 + -4 Reorder the terms: 4 + -4 + -3p + p2 = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3p + p2 = 0 + -4 -3p + p2 = 0 + -4 Combine like terms: 0 + -4 = -4 -3p + p2 = -4 The p term is -3p. Take half its coefficient (-1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. -3p + 2.25 + p2 = -4 + 2.25 Reorder the terms: 2.25 + -3p + p2 = -4 + 2.25 Combine like terms: -4 + 2.25 = -1.75 2.25 + -3p + p2 = -1.75 Factor a perfect square on the left side: (p + -1.5)(p + -1.5) = -1.75 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 8y=4600 | | 5-4x-13=3 | | -1.5X=-6.25 | | (3/8)/(3/4)=x | | 16-5m-4m-2+2m= | | 3/8/3/4=x | | x/-5+29=12 | | (2+2x+9x^2+4x^3)-(-1+2x-9x^2+4x^3)= | | 4x+45=144 | | 2(10)-y=19 | | g+(g+8)+(g+8)+(g+8)+(g+8)=200 | | 3(x+8)-11x=-8(x+4)-11 | | -21+2x=24-3x | | x-9=6x+9 | | 1=7x+8 | | 1=s-23 | | 20(x-80)=40 | | -16=-18x | | 4p^2-60p+400=0 | | -4y+10=4+9y | | -2(t-2)+4t=5t-3 | | 59=9x-4 | | 40=10-5x | | X+(3x-4)(-2)=10 | | -5(t-4)+9t=8t-6 | | 400=4p(18-(3+p)) | | (2x-1)(x-4)+(x-5)(x-5)-(x-4)(3x-4)=-11 | | y+3=-1/4 | | x^2+3600=150x | | 0=4x-9 | | 20-(-4)+1= | | -4t+16+8t=7t-4 |

Equations solver categories